2020
DOI: 10.1016/j.neuroimage.2020.117360
|View full text |Cite
|
Sign up to set email alerts
|

Associations between stress exposure and new mothers’ brain responses to infant cry sounds

Abstract: Exposure to severe stress has been linked to negative postpartum outcomes among new mothers including mood disorders and harsh parenting. Non-human animal studies show that stress exposure disrupts the normative adaptation of the maternal brain, thus identifying a neurobiological mechanism by which stress can lead to negative maternal outcomes. However, little is known about the impact of stress exposure on the maternal brain response to infant cues in human mothers. We examined the association of stress expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 103 publications
(129 reference statements)
1
17
0
Order By: Relevance
“…The functional magnetic resonance imaging (fMRI) paradigm has been previously validated in multiple samples of new mothers during the postpartum period, and a subset of these data from the Infant Development, Environment and Attachment cohort has been reported ( N = 27 and N = 53) ( Kim et al. , 2016 , 2020 ). fMRI task was a block design with 10 20 s blocks of each stimulus type in counterbalanced order (own/other cry/white-noise stimuli), with implicit baseline modeled over two runs ( \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\sim$\end{document} 10 min per run for a total of 20 min).…”
Section: Methodsmentioning
confidence: 99%
“…The functional magnetic resonance imaging (fMRI) paradigm has been previously validated in multiple samples of new mothers during the postpartum period, and a subset of these data from the Infant Development, Environment and Attachment cohort has been reported ( N = 27 and N = 53) ( Kim et al. , 2016 , 2020 ). fMRI task was a block design with 10 20 s blocks of each stimulus type in counterbalanced order (own/other cry/white-noise stimuli), with implicit baseline modeled over two runs ( \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\sim$\end{document} 10 min per run for a total of 20 min).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence of increased perinatal risk for psychopathology among parents suggests this may be a period of vulnerability for stress‐related modifications in adaptive parenting responses (Aktar et al., 2019; Barba‐Müller et al., 2019; Kim, 2020; Vismara et al., 2016). Stress has been shown to influence parent (primarily maternal) and infant development through physiological effects related to HPA‐axis activation during pregnancy (Coussons‐Read, 2013; Curley & Champagne, 2016), but prenatal perceived stress may importantly alter caregiving in expectant mothers and fathers by disrupting adaptive neurobiological and psychological reorganization related to positive parent–infant dyad development (Gholampour et al., 2020; Hoekzema et al., 2017; Kim et al., 2020; Rutherford & Mayes, 2017; Rutherford et al., 2018). In the current study, we found that higher levels of prenatal perceived stress were associated with a larger LPP response to low‐distress infant cries.…”
Section: Discussionmentioning
confidence: 99%
“…Although parents generally report increased stress during the perinatal period, with mothers reporting higher levels of perinatal stress than fathers, less is known regarding prenatal stress and associated neurodevelopment in parents (Coussons‐Read, 2013). It has been suggested that prenatal maternal stress exposure is associated with postnatal neural processing of infant cries and sensitive caregiving (Kim et al., 2020), and individual differences in prenatal stress may predict postnatal psychopathology among parental couples (Vismara et al., 2016). Therefore, understanding the impact of perceived stress on neural responses to infant cries prenatally in women and men could provide clinical insight into sensitive periods associated with perinatal neurobiological reorganization and stress susceptibility, ultimately informing targeted prenatal support and early interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Patients with a history of serious violence can be seen lower GMV in the right inferior temporal area (the anterior part of the right inferior temporal gyrus expanded to the fusiform gyrus, the middle temporal gyrus, and the temporal pole) and the right [18]. I area (the right insula increases to the ventral diencephalon) than those without a history of violence after controlling for lower years of education and higher positive symptom records [19]. The right inferior temporal area which consists of temporal pole and the central temporal gyrus, and the right insular area were showed in this study as associated with violent behavior.…”
Section: Prevalence and Epidemiologymentioning
confidence: 95%